2017
DOI: 10.1530/edm-17-0104
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadotropic hypogonadism in human immunodeficiency virus-infected men: uncommonly low testosterone levels

Abstract: Hypogonadotropic hypogonadism (HH) is common and occurs prematurely in HIV-infected men. However, HH with very low testosterone has not been described. Three men with normal pubertal development and HIV1 diagnosis at the ages of 22, 34 and 35 years. All complained of decreased libido, anejaculation and erectile dysfunction thirteen years, six months and one year after HIV diagnosis, respectively. Two had depressive syndrome and two were treated with antiretroviral therapy. Laboratory tests revealed isolated HH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Here, we hypothesize that the virus-host interaction mechanism in males is different, and more acutely linked to SARS-CoV-2 infection per se. Indeed, a sex different sensitivity of the hypothalamic-pituitary-gonadal (HPG) to inflammation 6,41,42 could induce an acute and dramatic drop in circulating tT in SARS-CoV-2 infected males, and the subsequent hypogonadal condition may trigger serious or an even fatal course of the disease. [28][29][30] According to our speculation, published data showed that circulating tT levels may be negatively affected by unmodifiable conditions (ie, age), 27,35 chronic conditions (ie, obesity, systemic diseases, and overall health status), 35,41 but also by acute illness, 35 including acute viral infections.…”
Section: Detection Of Covid-19 In the Male Reproductive Tractmentioning
confidence: 99%
“…Here, we hypothesize that the virus-host interaction mechanism in males is different, and more acutely linked to SARS-CoV-2 infection per se. Indeed, a sex different sensitivity of the hypothalamic-pituitary-gonadal (HPG) to inflammation 6,41,42 could induce an acute and dramatic drop in circulating tT in SARS-CoV-2 infected males, and the subsequent hypogonadal condition may trigger serious or an even fatal course of the disease. [28][29][30] According to our speculation, published data showed that circulating tT levels may be negatively affected by unmodifiable conditions (ie, age), 27,35 chronic conditions (ie, obesity, systemic diseases, and overall health status), 35,41 but also by acute illness, 35 including acute viral infections.…”
Section: Detection Of Covid-19 In the Male Reproductive Tractmentioning
confidence: 99%
“…Furthermore, a study on testicular autopsy reported the gradual destruction of germ cells in extended AIDS survival (Shevchuk, Pigato, Khalife, Armenakas, & Fracchia, 1999). Males who used more advanced immunosuppressants had reduced levels of total serum testosterone, caused by secondary hypogonadism (Gomes, Aragüés, Guerra, Fernandes, & Mascarenhas, 2017), and the latter is one of the significant endocrine disorders causing infertility in men with AIDS (Wong, Levy, & Stephenson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, PLWH are commonly affected by disruptions to the hypothalamic-pituitary-adrenal (HPA) and -gonadal (HPG) axes. 91,92…”
Section: Hiv Effec Ts On Hyp Othal Ami C-pituitary-adrenal and -Gonad...mentioning
confidence: 99%